COHERENCE AND COHESION OF STUDENTS’ ANSWERS TO QUESTIONS IN SPEAKING TEST AT LITERATURE FACULTY IN UNIVERSITY OF PUTERA BATAM - Gaguk Rudianto (BASIS (Bahasa dan Sastra Inggris), 2016)
This research is conducted to give description about coherence and cohesion of the students answers to speaking final exam in Putera Batam University. Data of this research comes from any written and electronic sources about coherence and cohesion. They are in the form of audio file. The data are transcribed and categorized into two grand categories namely coherence and cohesion. From both grand categories, they are broken down until sub-sub categories which do not contain more than 10 data, then they are analyzed in order to draw some substantive theories. From substantive theories arising, then they are grouped into two grand substantive theories. They are 1) Correct grammatical aspect in every component of a sentence can make cohesion of the sentence. 2) Combination of cohesive sentences in an answer can determine the cohesive answers. The method of collecting data in this research by recording students’ answers to final exam of speaking subject.